Temporal Myositis with Middle Fossa Epidural Abscess as the Complications of Acute Otitis Media - Jamaluddin, Jamal Sazly; Daud, Mohd Khairi Md; Rabi, Mahedzan Mat (Bangladesh Journal of Medical Science, 2012)
Acute otitis media is an inflammatory process involving the mucoperiosteum of the middle ear cleft. The clinical spectrum can be extended from a self-limiting benign condition to a complicated disease with intracranial involvement. Intracranial and extracranial complications of acute otitis media is still occur in the modern antibiotic era and has potentially serious consequences with high mortality rate. We report a case of acute otitis media with temporal myositis and middle fossa epidural abscess which is rarely seen as the complications from the disease. DOI: http://dx.doi.org/10.3329/bjms.v11i2.8472 Bangladesh Journal of Medical Science Vol. 11 No. 02 April 2012: 126-128